ANALYSIS OF HUMAN RESOURCE LIMITATIONS ON TEACHERS MADRASAH TSANAWIYAH AL-FURQON BANDUNG - Fitria, Ida Jalilah; Rifan, Mochamad (PT. Altin Riset Publishing, 2024)
This study aims to explore the impact of limited human resources (HR) on the quality of teaching and learning at Madrasah Tsanawiyah Al-Furqon through interviews with two teachers. The results indicate that the insufficient number of teaching staff increases the workload of teachers, requiring them to handle excessive administrative tasks and teach subjects outside their specialization. This condition negatively impacts the quality of education, as teachers struggle to provide adequate attention to each student, especially those requiring more intensive guidance. The HR limitations also hinder students' academic and non-academic achievements, as well as the implementation of development programs such as extracurricular activities. Although teachers have attempted to address these challenges by utilizing interactive and project-based learning methods, support from school management in the form of additional teacher recruitment, training, and educational technology is still needed to effectively meet teaching needs and maintain teacher well-being. This study underscores the importance of greater attention to HR management in educational settings to ensure optimal and sustainable learning processes.